2008
DOI: 10.4269/ajtmh.2008.79.93
|View full text |Cite
|
Sign up to set email alerts
|

Human Toxocariasis in Rural Brazilian Amazonia: Seroprevalence, Risk Factors, and Spatial Distribution

Abstract: Abstract. This population-based cross-sectional study of 403 rural settlers in Brazilian Amazonia revealed an overall rate of IgG seropositivity to Toxocara canis excretory-secretory larval antigen of 26.8% (95% confidence interval [CI], 22.5-31.4%). Multilevel logistic regression analysis identified current infection with hookworm (odds ratio [OR], 2.32; 95% CI, 1.11-4.86) and residence in the most recently occupied sectors of the settlement (OR, 1.81; 95%CI, 1.3-2.52) as significant risk factors for Toxocara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 37 publications
(50 reference statements)
4
34
1
2
Order By: Relevance
“…The influence of cat ownership on a positive ELISA test has been less studied. In recent serosurveys in Brazil, having a cat was identified as both a protective factor and a risk factor [33,34] . A third survey in Poland [31] , but not a large country-wide study in the United States [25] found cat ownership to be a significant predictor of Toxocara seropositivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of cat ownership on a positive ELISA test has been less studied. In recent serosurveys in Brazil, having a cat was identified as both a protective factor and a risk factor [33,34] . A third survey in Poland [31] , but not a large country-wide study in the United States [25] found cat ownership to be a significant predictor of Toxocara seropositivity.…”
Section: Discussionmentioning
confidence: 99%
“…However, having a pet was not considered a risk/protective factor for toxocariasis. Keeping a dog in a household has been recognised as a risk factor in some [31,32] but not all surveys [21,33] . The influence of cat ownership on a positive ELISA test has been less studied.…”
Section: Discussionmentioning
confidence: 99%
“…10,[24][25][26][27][28][29][31][32][33][34][36][37][38][39][40][41][42][43][44] One study did not describe the diagnostic methodology applied. 35 As T. canis and T. cati cannot be distinguished serologically, we identified the study population as having toxocariasis.…”
Section: Resultsmentioning
confidence: 99%
“…The different reports indicate seroprevalence rates ranging from 2.8 % to 54.8 %, identifying associated risk factors with the presence of antibodies anti-Toxocara, in which stands the classicallyknown frequent contact with contaminated soils, interaction with dogs, bad hygiene habits, and in association with the last factor, socioeconomic conditions [38][39][40][41][42][43][44][45][46].…”
Section: Toxocariasis In Brazilmentioning
confidence: 99%